2017
DOI: 10.5380/rf.v47i4.54471
|View full text |Cite
|
Sign up to set email alerts
|

CARACTERIZAÇÃO ANATÔMICA E DESCRIÇÃO FÍSICO-QUÍMICA E MECÂNICA DA MADEIRA DE Mimosa schomburgkii

Abstract: ResumoO uso de madeira de espécies alternativas na construção civil é uma alternativa para reduzir a utilização concentrada em poucas espécies e evitar a falta de matéria prima no mercado. Diante do exposto, o objetivo deste estudo foi avaliar propriedades físicas, químicas, anatômicas e mecânicas da madeira de Mimosa schomburgkii visando identificar o seu potencial para o uso na construção civil. Foi utilizada a madeira de Mimosa schomburgkii, com idade de 33 anos. As características anatômicas avaliadas fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The average compressive strength parallel to the grain (f c,0k ) was 78 MPa, close to the result obtained by Grobério and Lahr (77.5 MPa) [12] with the same wood specie and higher when compared with Mimosa tenuiflora (58.25 MPa) [13], Mimosa schomburgkii (64.7 MPa) [4], Toona ciliata (27 MPa) [14], Eucalyptus camaldulensis (25.3 MPa) [15] e Eucalyptus benthamii (37.34 MPa) [16].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The average compressive strength parallel to the grain (f c,0k ) was 78 MPa, close to the result obtained by Grobério and Lahr (77.5 MPa) [12] with the same wood specie and higher when compared with Mimosa tenuiflora (58.25 MPa) [13], Mimosa schomburgkii (64.7 MPa) [4], Toona ciliata (27 MPa) [14], Eucalyptus camaldulensis (25.3 MPa) [15] e Eucalyptus benthamii (37.34 MPa) [16].…”
Section: Resultssupporting
confidence: 86%
“…Among the sectors that use wood as raw material, civil construction sector is the one of the most exigent in terms of physical and mechanical properties. Then, it causes a certain limitation in the number of wood species with characteristics that could be used in this sector [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…High holocellulose and lignin contents in non-treated wood can affect the material's mechanical properties. Costa et al (2017) reported that the mechanical strength of wood to some types of loads is not associated only with thickness, but also with the amounts of their chemical components, such as cellulose, hemicellulose, lignin, and the percentages of extractives in the lumen. Gomes et al (2021) reported that renewable lignocellulosic materials tend to present different cellulose, hemicellulose, and lignin compositions and that these chemical properties are factors that can limit the material applicability.…”
Section: Colorimetric Parametersmentioning
confidence: 99%
“…The variations that occur in the anatomical parameters of wood change the dimensions and frequency of the cells, thus directly affecting its physical and mechanical properties (COSTA et al, 2017). Mechanical strength can be determined from static bending, compression, and hardness tests, in which the mechanical parameters of the material reflect the existing relationship between the response or deformation when subjected to a stimulus or force (KOL et al, 2017).…”
Section: Introductionmentioning
confidence: 99%